The only restriction for x is that the value inside the square root must be greater than 0.
We can write
\(6-x-x^2-2x^2 \geq 0\)
Solving for x, we have
\(-3x^2-x+6 \geq 0\)
Completing the square, we have
\(-3\left(x+\frac{1}{6}\right)^2+\frac{73}{12}\ge \:0\)
\(-3\left(x+\frac{1}{6}\right)^2\ge \:-\frac{73}{12}\)
\(\left(x+\frac{1}{6}\right)^2\le \frac{73}{36}\)
Square rooting both sides, we get
\(-\sqrt{\frac{73}{36}}\le \:x+\frac{1}{6}\le \sqrt{\frac{73}{36}}\)
\(\frac{-\sqrt{73}-1}{6}\le \:x\le \frac{\sqrt{73}-1}{6}\)
So the domain is \(\frac{-\sqrt{73}-1}{6}\le \:x\le \frac{\sqrt{73}-1}{6}\)
Thanks! :)